THE EFFECTIVENESS OF GREEN TEA AND MORINGA TEA ON THE LEVEL OF DYSMENORRHEA PAIN IN ADOLESCENTS - Intani Ega Rarassari; Ribkha Itha Idhayanti; Siti Chunaeni (Poltekkes Kemenkes Semarang, 2021)
Background: According to the World Health Organization (WHO) in Indonesia, the incidence of dysmenorrhea is 55% in productive age, 15% of them complain of limited activity due to dysmenorrhea. Forms the results of a preliminary study conducted, it's showed that the results of interviews with young women showed that 60% of adolescents experienced dysmenorrhea, 20% sometimes, and 20% did not experience dysmenorrhea. Dysmenorrhea is a problem for teenagers in carrying out their daily activities, especially in the learning process.The purpose of this study was to determine the effectiveness of green tea and moringa tea on reducing the level of dysmenorrhea pain in adolescentsMethods: This design of research uses a quasi-experimental approach with a two-group pretest-posttest design approach. The population 40 and sample 32 respondents with an accidental sampling technique.Results: In this study, it was found that moringa is effective in reducing the pain of dysmenorrhea. With the results of the Mann-Whitney test p-value = 0.031. moringa tea more effective than green teaConclusion: . In this study, it is hoped that adolescents can optimize non-pharmacological therapy by consuming moringa tea to reduce dysmenorrhea